1985
DOI: 10.1176/ajp.142.8.905
|View full text |Cite
|
Sign up to set email alerts
|

Extended sleep (hypersomnia) in young depressed patients

Abstract: To test the hypothesis that young depressed patients have prolonged rather than shortened sleep, 14 depressed patients aged 17-25 and age-matched normal control subjects were allowed to sleep as long as they wanted. All subjects increased their sleep over baseline values, but the extended sleep period of the depressed patients was almost twice as long as that of the control subjects. The distribution of sleep stages in the extended period did not differ. The depressed patients had changes in the length of REM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The vast majority of clinical and research polysomnograms are not performed allowing the patient to go to bed and wake on their own accord, most likely due to logistical difficulties encountered when patients sleep well into the day. However, as demonstrated by these results and by prior studies, extended polysomnographic recordings are likely invaluable in quantifying hypersomnolence, particularly when it is comorbid with a mood disorder (Hawkins et al ., 1985). In addition, our actigraphic measures substantiate that increased sleep duration in participants with depression and comorbid hypersomnolence relative to controls can also be documented outside of the sleep laboratory, and that results of polysomnography were not likely due to sleep deprivation prior to in-laboratory assessment.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The vast majority of clinical and research polysomnograms are not performed allowing the patient to go to bed and wake on their own accord, most likely due to logistical difficulties encountered when patients sleep well into the day. However, as demonstrated by these results and by prior studies, extended polysomnographic recordings are likely invaluable in quantifying hypersomnolence, particularly when it is comorbid with a mood disorder (Hawkins et al ., 1985). In addition, our actigraphic measures substantiate that increased sleep duration in participants with depression and comorbid hypersomnolence relative to controls can also be documented outside of the sleep laboratory, and that results of polysomnography were not likely due to sleep deprivation prior to in-laboratory assessment.…”
Section: Discussionmentioning
confidence: 60%
“…Reasons full-text articles were excluded are detailed in Figure 2. Seven studies (in addition to the current study) were identified via systematic review for inclusion in meta-analyses (Dolenc et al ., 1996; Hawkins et al ., 1985; Hiyama, 1982; Plante et al ., 2012; Quitkin et al ., 1985; Thase et al ., 1989; Vgontzas et al ., 2000) (Table 5). Three of these studies had reports of ad libitum total sleep time, while seven either reported sleep efficiency or provided sufficient data to derive this variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, depression is a common disease and has become increasingly prevalent in the world [ 1 ]. Most depressed people show evidence of one or more changes in sleep neurophysiology; i.e., some complain of insomnia and the others suffer from hypersomnia [ 2 , 3 ]; therefore, impaired sleep is a critical symptom of depressed patients. Gresham SC et al .…”
Section: Introductionmentioning
confidence: 99%
“…While delayed sleep-onset and frequent awakenings accompany almost any kind of insomnia, early morning awakening was considered to be specific for endogenous depression but this hypothesis was not confirmed (Reynolds and Kupfer, 1987). Although insomnia is the most frequent complaint, hypersomnia also has been observed (Garvey et al, 1984; Hawkins et al, 1985), particularly in individuals with bipolar depression (Parker et al, 2006; Thase et al, 1989). …”
Section: Subjective Sleep Measures and Depressionmentioning
confidence: 99%